Infants Are Exposed to Human Milk Oligosaccharides Already in utero - Wise, Audra; Robertson, Bianca; Choudhury, Biswa; Rautava, Samuli; Isolauri, Erika; Salminen, Seppo; Bode, Lars (Frontiers in Pediatrics, 2018)
Human milk oligosaccharides (HMOs) are complex carbohydrates that are highly abundant and, in their complexity, unique to human milk. Accumulating evidence indicates that exposure to HMOs in the postnatal period affects immediate as well as long-term infant health and development. However, studies reported in the 1970s showed that HMOs already appear in maternal urine and blood during pregnancy and as early as the first trimester. In this pilot study we aimed to determine whether or not HMOs also appear in amniotic fluid. We enrolled women during pregnancy and collected their urine and amniotic fluid at birth as well as their milk four days postpartum. We analysed the samples by HPLC and mass spectrometry and identified several HMOs including 2’-fucosyllactose, 3-fucosyllactose, difucosyllactose, and 6’sialyllactose to be present in different relative abundancies in all three tissues. This is the first report that HMOs appear in amniotic fluid and that the fetus is already exposed to HMOs in utero, warranting future research to investigate the immediate and long-term implications on fetal and infant health and development.